Optimal management of oropharyngeal and esophageal candidiasis in patients living with HIV infection - Jose A Vazquez (Dove Medical Press, 2010)
Jose A VazquezDivision of Infectious Diseases, Henry Ford Hospital, Wayne State University School of Medicine, Detroit, MI, USAAbstract: Mucocutaneous candidiasis is frequently one of the f irst signs of human immunodeficiency virus (HIV) infection. Over 90% of patients with AIDS will develop oropharyngeal candidiasis (OPC) at some time during their illness. Although numerous antifungal agents are available, azoles, both topical (clotrimazole) and systemic (fluconazole, itraconazole, voriconazole, posaconazole) have replaced older topical antifungals (gentian violet and nystatin) in the management of oropharyngeal candidiasis in these patients. The systemic azoles, are generally safe and effective agents in HIV-infected patients with oropharyngeal candidiasis. A constant concern in these patients is relapse, which is dependent on the degree of immunosuppression commonly seen after topical therapy, rather than with systemic azole therapy. Candida esophagitis (CE) is also an important concern since it occurs in more than 10% of patients with AIDS and can lead to a decrease in oral intake and associated weight loss. Fluconazole has become the most widely used antifungal in the management of mucosal candidiasis. However, itraconazole and posaconazole have similar clinical response rates as fluconazole and are also effective alternative agents. In patients with fluconazole-refractory mucosal candidiasis, treatment options now include itraconazole solution, voriconazole, posaconazole, and the newer echinocandins (caspofungin, micafungin, and anidulafungin).Keywords: oropharyngeal candidiasis, esophageal candidiasis, HAART, antifungal agents, HIV, AIDS